Persepsi Masyarakat Terhadap Peran Perempuan dalam Perawatan dan Peningkatan Ekonomi Keluarga di Masa Pandemi Covid-19 - Choirul Anam Firman Thohari; Dian Meiningtias (Marwah: Jurnal Perempuan, Agama dan Jender, 2021)
The world is experiencing a crisis due to the Covid-19 pandemic. This places women as the party most vulnerable to a decline in physical health and economic pressure, the fact is that violence against women has increased during the pandemic. On the other hand, women have an important role in improving the family economy during a pandemic, including contributions to family finances, family financial management, and family productivity. However, the important role of women in the family is often perceived differently by society. By 'the product', this study aims to survey people's perceptions of the role of women in improving the family economy during the Covid-19 pandemic and the influence of primary and secondary socialization on people's perceptions of the role of care and improving the family economy during the Covid-19 pandemic. This research method is a survey research method. This study found that only primary factors influence people's perceptions of the role of women in improving the family economy during the Covid-19 pandemic.